'A Blank slate body:' Cis individuals' descriptions of their androgynous body ideals. Issue 2 (3rd April 2022) - Cusack, Claire E.; Morris, Ezra R.; Galupo, M. Paz
ABSTRACT: Body image is typically studied through the framework of internalising gender binary standards of attractiveness. However, not all individuals adhere to traditional appearance norms. This study aimed to understand the meaning of cis (non-trans) individuals' androgynous or non-stereotypical body ideals and the actions they engage in to achieve these ideals. We recruited an online sample of 78 participants (42 cis women and 36 nonbinary individuals who also identified as cis). Participants responded to two open-ended prompts: 1) What does your androgynous or nonstereoypical body mean to you? and 2) What actions have you taken to achieve this ideal? Authors identified three overarching themes of what an androgynous body ideal meant to our participants. An androgynous appearance was central to participants' beauty standards, authenticity, and gender expression. To achieve or maintain an androgynous body ideal, participants described actions that altered their gender expression, primary and secondary sex characteristics, and body. Our findings underscore the way androgynous appearance ideals function to transgress binary gender in affirming ways to cis individuals. Further, recruiting on the basis of androgyny yielded a wider understanding of cis identity, as our participants were diverse across both sexuality (queer and heterosexual) and gender (women and nonbinary individuals).